Antenatal dexamethasone retarded fetal long bones growth and development by down-regulating of insulin-like growth factor 1 signaling in fetal rats. (7th January 2022) - Qiu, Junlan; Fan, Xiaorong; Ding, Hongmei; Zhao, Meng; Xu, Ting; Lei, Jiahui; Ji, Bingyu; Zhuang, Zhixiang; Gao, Qinqin
Objective: Dexamethasone (DEX), a synthetic glucocorticoid, has been widely used as a medication for premature delivery. However, the side effects of antenatal DEX treatment on fetal bone development, as well as the underlying mechanisms still remain to be elucidated. Here, we aimed to explore the effects and the related mechanisms of antenatal DEX exposure during late pregnancy on fetal bone growth and development. Methods: Pregnant Sprague–Dawley rats were randomly divided into DEX group and vehicle group from gestational day 14 (GD14). Pregnant rats in DEX group were intraperitoneally injected once with DEX (200 µg/kg body weight) on GD14, 16, 18, and 20. The vehicle group rats were administered the same amount of normal saline at the same time. Pregnant rats were anesthetized at GD21 to harvest fetal femurs for analysis. Results: Antenatal DEX treatment delayed fetal skeletal growth via inhibiting extracellular matrix (ECM) synthesis and downregulating insulin-like growth factor 1 (IGF1) signaling. Several components of IGF1 signaling pathway, including IGF1 receptor, insulin receptor substrate, as well as serine–threonine protein kinase, were down-regulated in fetal growth plate chondrocytes following DEX treatment. Conclusion: This study indicated that antenatal DEX treatment-retarded fetal skeletal growth was associated with the down-regulation of IGF1 signaling in growth plate chondrocytes, providing important information about the impact of antenatal DEX application four courses on premature infant.